Assessment of Medication Related Problems in Geriatrics Unit of Nigerian Tertiary Hospital - Mgbahurike A. A; Wonte M. I. (Journal of Medical Biomedical and Applied Sciences, 2020)
Medication related problems are prevalent especially in the geriatric populationandcancause considerable patient morbidity and in some cases death as well as increased health expenditure. The elderly population is at increased risk for medication related problems as a result of age – related physiological changes and the presence of multiple chronic diseases. Aim: This study aimed to assess medication related problems (MRP) in University of Port Harcourt Teaching Hospital, with the objective to identify and categorize the MRP according to types as well as identify the most frequent MRP encountered and interventions made by the pharmacists. Method: The study was a retrospective study carried out among 200 geriatric patientsrandomly sampled, over 18months period (January 2018 to June 2019). Data extracted include patients’ demographic information, prescribed medication and number, medical condition, and pharmacist’s intervention (where available) using data collection form. Information collected were categorized and analyzed statistically. Result: showed that female geriatric patients (64.4%) were more than male (35.5%). Most (43%) of the studied population were in the range of 60yrs – 70yrs. Out of the 200 patients assessed, 157 (78.4%) had medication related problems. Drug- drug interaction was the most frequently (64.4%) occurred MRP, as most (62.5%) of the studied group had 6 -10 medications in one prescription, and 12.5% had more than 10 medications in one prescription. Following drug interaction was incorrect drug administration (18.5%). Of the population studied, 56.5% of the patients were using their medication inappropriately. The major contributing factors responsible for these MRPs were comorbidities, poly-pharmacy, and medication non- adherence. Conclusion: The study identified categories of medication related problem in the geriatric Unit of the hospital and the need for pharmacists’ interventions.